The Effectiveness of Lectures in the Emergency Period for the Spread of Covid-19 - Ahmad Hanany Naseh (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2021)
LECTURE EFFECTIVENESS DURING THE EMERGENCY OF THE SPREAD OF COVID-19. The pandemic problem facing the world brings change into a new era. Everything is being done to break the chain of transmission of COVID-19. One of them is in the world of education, online learning methods have changed. The purpose of this article is to understand the effectiveness of online lectures in the emergency period of the COVID-19 outbreak. This research is a library research, specifically focusing on journals and books related to the research theme. The results showed that there were students who agreed with the online learning method, but there were students who did not agree. It has been found that the main problems of online lectures are lack of technical mastery, unstable network, higher costs, and the emergence of psychological problems in students.